Synthetic, structural mimetics of the β-hairpin flap of HIV-1 protease inhibit enzyme function. Issue 21 (1st November 2015) - Chauhan, Jay; Chen, Shen-En; Fenstermacher, Katherine J.; Naser-Tavakolian, Aurash; Reingewertz, Tali; Salmo, Rosene; Lee, Christian; Williams, Emori; Raje, Mithun; Sundberg, Eric; DeStefano, Jeffrey J.; Freire, Ernesto; et al.
Graphical abstract: Abstract: Small-molecule mimetics of the β-hairpin flap of HIV-1 protease (HIV-1 PR) were designed based on a 1, 4-benzodiazepine scaffold as a strategy to interfere with the flap–flap protein–protein interaction, which functions as a gated mechanism to control access to the active site. Michaelis–Menten kinetics suggested our small-molecules are competitive inhibitors, which indicates the mode of inhibition is through binding the active site or sterically blocking access to the active site and preventing flap closure, as designed. More generally, a new bioactive scaffold for HIV-1PR inhibition has been discovered, with the most potent compound inhibiting the protease with a modest K i of 11 μM.